Certification of a RIA-Lab according to DIN EN ISO 9001:2000 - Moser, E.; Markowetz, D.; Schächtele, S. (Nuklearmedizin - NuclearMedicine, 2002)
The university hospital Freiburg intends to establish step by step a total quality management system (TQMS) in all facilities with an external certification as its final aim. This has been reached already in the central laboratory. Therefore, it is effective for the department of nuclear medicine to do the same for its own lab specialized in thyroid hormones. The TQMS has been built up within six months on the basis of DIN EN ISO 9001:2000. This internationally accepted standard is of uttermost economical importance for an institution situated near the French and Swiss border.This review describes the procedure in detail. Responsible for the effort were the engagement of the coworkers in the lab as well as an adequate choice of the external adviser and the authority for certification. The procedure is formalized to a high degree and much understanding for analytic thinking and systematization is needed. Now it remains to be seen, if the desired effect (increased understanding for quality within the department, more efficient performance of the lab, better acceptance by the clients) will arise.
Keywords: TQMS; quality management system; certification; RIA-Lab